2015
DOI: 10.1002/ijc.29690
|View full text |Cite
|
Sign up to set email alerts
|

RUNX3 and CAMK2N1 hypermethylation as prognostic marker for epithelial ovarian cancer

Abstract: Treatment of epithelial ovarian cancer consists of surgery plus platinum-taxane based chemotherapy. Neither prognostic nor predictive serum or tissue markers except BRCA1/2 mutations are available thus precluding individualized treatment. Aim of this study is the identification and validation of DNA-methylation markers with prognostic value. Genome-wide array analyses were used to determine methylation patterns in groups of serous EOC with different outcome (PFS < vs. > 3 years, each n 5 6) but comparable clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 51 publications
1
51
0
Order By: Relevance
“…Higher resolution methylation arrays: Illumina’s Human Methylation 27 K, Human Methylation 450 K, and custom microarrays, have been utilized in the past seven years in studies with larger sample numbers [11,12,20,6971] (Table 1). The Cancer Genome Atlas (TCGA), collaboration between the National Cancer Institute and National Human Genome Research Institute, has profiled the genomes of 33 types of cancer, including ovarian cancer.…”
Section: Dna Methylation Analyses In Eocmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher resolution methylation arrays: Illumina’s Human Methylation 27 K, Human Methylation 450 K, and custom microarrays, have been utilized in the past seven years in studies with larger sample numbers [11,12,20,6971] (Table 1). The Cancer Genome Atlas (TCGA), collaboration between the National Cancer Institute and National Human Genome Research Institute, has profiled the genomes of 33 types of cancer, including ovarian cancer.…”
Section: Dna Methylation Analyses In Eocmentioning
confidence: 99%
“…Huang et al [95] identified differential methylated regions (DMR) associated with progression-free survival (PFS), and validated the DMR in platinum resistant and sensitive cell lines. Hafner et al [71] evaluated DNA methylation difference between pools of HGSOC DNA with poor or good survival followed by validation in an independent set of samples revealing two genes, RUNX3 and CAM21, to be associated with PFS. In cell lines, increased methylation of these two genes was associated with reduced gene expression.…”
Section: Clinical Aspects Of Epigenetics In Eocmentioning
confidence: 99%
“…Our study is the first to outline a role for miR-182-5p in the proliferation of OSCC cells. The CAMK2N1 gene, a calcium/calmodulin-dependent protein kinase II inhibitor, is a known potent modulator of tumorigenesis and subsequent tumor growth [15]. CAMK2N1 expression may have a tumor suppressing role in certain cancers, and its dysregulation has been linked to tumorigenesis [25].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%
“…miR-182-5p and U6 primers were designed by and purchased from RiboBio Co., Ltd. (Guangzhou, China). CAMK2N1 primer sequences were designed following the procedures described in Hafner et al [15].…”
Section: Cell Line Culturementioning
confidence: 99%
“…Abnormal DNA methylation may serve as a biomarker for early detection, outcome prediction, and individualized treatment . Hypermethylation of several genes, including those involved in DNA repair, AKT/mTOR, redox, apoptosis, cell adhesion and cancer stem cell signaling pathways, was reported to correlate with poor prognosis in ovarian cancer patients. Those epigenetics signatures revealed EOC heterogeneity and prognostic carcinogenesis that probably initiate by the diversity of genetic mutations .…”
mentioning
confidence: 99%